Dampak Pola Asuh Otoriter Orang Tua terhadap Kehidupan Sosial Anak di Dusun Rejo Mulyo Aceh Tamiang - Rahmat Syaibani; Rodia Afriza; Putri Chintya Sari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In this study, parents as the child's closest environment have an important role in supporting child development. One of the things that can support the child's development is the pattern of caring adopted by parents. The pattern of caring is the relationship or patterns of interaction between parents and children in order to meet the physical and psychological needs of children. The Pattern of Caring is divided into three types, one of which is authoritarian. These problems arise as a result of children being subjected to excessive restrictions and pressure in the family environment. There is a huge influence on the social life of the child by the authoritarian pattern of parental care. Where there are many negative influences on the social life of the child. Children are less sociable because they feel insecure and tend to be quiet. Children are afraid to make mistakes and to try new things.